Hyperbranched TiO2–CdS nano-heterostructures for highly efficient photoelectrochemical photoanodes. (13th June 2018) - Mezzetti, Alessandro; Balandeh, Mehrdad; Luo, Jingshan; Bellani, Sebastiano; Tacca, Alessandra; Divitini, Giorgio; Cheng, Chuanwei; Ducati, Caterina; Meda, Laura; Fan, Hongjin; Di Fonzo, Fabio
Abstract: Quasi-1D-hyperbranched TiO2 nanostructures are grown via pulsed laser deposition and sensitized with thin layers of CdS to act as a highly efficient photoelectrochemical photoanode. The device properties are systematically investigated by optimizing the height of TiO2 scaffold structure and thickness of the CdS sensitizing layer, achieving photocurrent values up to 6.6 mA cm −2 and reaching saturation with applied biases as low as 0.35 VRHE . The high internal conversion efficiency of these devices is to be found in the efficient charge generation and injection of the thin CdS photoactive film and in the enhanced charge transport properties of the hyperbranched TiO2 scaffold. Hence, the proposed device represents a promising architecture for heterostructures capable of achieving high solar-to-hydrogen efficiency.